2023
DOI: 10.1017/s0013091523000093
|View full text |Cite
|
Sign up to set email alerts
|

Higher order log-concavity of the overpartition function and its consequences

Abstract: Let ${\overline{p}}(n)$ denote the overpartition function. In this paper, we study the asymptotic higher-order log-concavity property of the overpartition function in a similar framework done by Hou and Zhang for the partition function. This will enable us to move on further in order to prove log-concavity of overpartitions, explicitly by studying the asymptotic expansion of the quotient ${\overline{p}}(n-1){\overline{p}}(n+1)/{\overline{p}}(n)^2$ up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is worth noting that despite the fact that the former proof requires more sophisticated preparation than the latter one, the method which we use there might be also effectively applied for more complicated functions like the partition function [22] or the overpartition function [28].…”
Section: Krystian Gajdzicamentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that despite the fact that the former proof requires more sophisticated preparation than the latter one, the method which we use there might be also effectively applied for more complicated functions like the partition function [22] or the overpartition function [28].…”
Section: Krystian Gajdzicamentioning
confidence: 99%
“…Moreover, these authors used that result and proved that the partition function p(n) is (asymptotically) r-logconcave for each r ∈ N + , for more details see [22]. Afterwards, Mukherjee, Zhang and Zhong [28] applied the aforementioned criterion and showed that the overpartition function is (asymptotically) r-log-concave for any r ∈ N + . Recall that an overpartition [9] of an integer n is a partition of n where the őrst occurrence of every distinct part may be overlined.…”
Section: Introductionmentioning
confidence: 99%